2013
DOI: 10.1111/ap.12024
|View full text |Cite
|
Sign up to set email alerts
|

Towards Positive Adaptive Change: The Association of Three Typologies of Agency With Motivational Factors

Abstract: There have been many models of change, and generally they involve eight major factors: openness to opportunity, visualisation, planning, action, closure, social support, inner drive, and management of negative emotions. In this article, the question of whether groups of people vary in their application of these factors is considered. Using responses from 248 participants (154 females and 94 males; aged 18-79), cluster analysis was used to show the number of factors that are used in change scenarios. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 60 publications
3
20
1
2
Order By: Relevance
“…On the one hand, this finding could indicate that the mentioned resilience competence is most important in teacher training; on the other hand, it could be a result of sample selection. Interestingly, the three manifestations of resilience competencies showed striking similarities to the study of Bowles and Arnup ( 2016 ) and a former study conducted by Bowles and Hattie ( 2013 ). Bowles and Arnup ( 2016 , p. 147) investigated “the link between adaptive functioning and resilience in early career teachers.” The authors identified three typologies of adaptability—stabilizers, adapters, and innovators—and showed that resilience is strongly associated with these typologies of adaptive change.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…On the one hand, this finding could indicate that the mentioned resilience competence is most important in teacher training; on the other hand, it could be a result of sample selection. Interestingly, the three manifestations of resilience competencies showed striking similarities to the study of Bowles and Arnup ( 2016 ) and a former study conducted by Bowles and Hattie ( 2013 ). Bowles and Arnup ( 2016 , p. 147) investigated “the link between adaptive functioning and resilience in early career teachers.” The authors identified three typologies of adaptability—stabilizers, adapters, and innovators—and showed that resilience is strongly associated with these typologies of adaptive change.…”
Section: Discussionsupporting
confidence: 74%
“…Further, no statements about the assumed alterable nature of the described resilience competencies (i.e., in terms of learnability) can be made on the basis of cross-sectional data. Although we cannot draw any causal conclusions from our study, we were able to show that there are basically three manifestations of resilience competencies among VET (trainee) teachers in Germany, which are closely related to the concept of adaptive change (see Bowles and Hattie, 2013;Bowles and Arnup, 2016). In order to investigate causal relationships between resilience competencies and occupational stress in teacher training, as well as the development of resilience competencies in the course of time, a longitudinal study design or an experimental design is needed.…”
Section: Limitations Of the Studymentioning
confidence: 77%
“…Similarly, leaders or managers who supported innovation tended to take a promotion focus (playing to win; Poskela & Martinsuo, 2009 ), rather than a loss prevention focus (playing not to lose; Manimala, Jose, & Thomas, 2006 ; Poskela & Martinsuo, 2009 ), thereby taking calculated risks and enabling their followers to do the same (Bowles & Hattie, 2013 ; Koch et al, 2015 ; Maria Stock, Zacharias, & Schnellbaecher, 2017 ; Sergeeva & Zanello, 2018 ; Spanjol & Tam, 2010 ). While a majority of studies found that the effect of champions was significant, Chen, Li, and Leung ( 2016 ) pointed out that two recent meta-analyses revealed that champions only had a small effect on the quantity of innovation by individuals.…”
Section: Results For Expectancies In the Literature: Can I Do This?mentioning
confidence: 99%
“…(Brennan, 2013). Par ailleurs, la communauté devrait refléter les différents niveaux de participations possibles : stabilisateur, modérateur, innovateur (Bowles et Hattie, 2013); participants leaders, participants actifs, participants en périphérie (Wenger, Mcdermott et Snyder, 2002). Même si les participants en périphérie agissent plutôt comme des observateurs, ils ne seraient pas pour autant passifs.…”
Section: Participation à La Communauté De Pratiqueunclassified
“…Le Tableau 1 présente la synthèse portant sur les niveaux de participation. (Bowles et Hattie, 2013;Brennan, 2013;Jarvela et Hadwin, 2013;Wenger et coll., 2002;Wenger et Trayner-Wenger, 2015) Interactions entre les participants de la communauté. Les espaces sociaux en ligne contiennent différentes fonctionnalités permettant l'interaction entre les participants.…”
Section: Participation à La Communauté De Pratiqueunclassified